The Effect of Intrinsic Motivation and Religiosity to Social Media Awareness around 'Fodamara Tv' Youtube Team - Nurfauzy Lubis; Rubino Rubino; Nur Hanifah (Universitas Nurul Jadid, 2022)
One of the youth mosque communities that are moving to become virtual preachers is Forum Pemuda Masjid Raya (Fodamara) Senapelan, Pekanbaru. They started their da'wah activism on social media through the